POTENTIAL PROBLEMS WITH PEER RESPONDING IN EFL WRITING CLASSES - Dilyorjon Solidjonov (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
In English as a Foreign Language (EFL) writing classes, peer responding has gained popularity as an effective technique for improving students' writing skills. Peer responding involves students providing feedback on each other's written work, allowing them to develop their writing skills through collaboration and active learning. While peer responding offers numerous benefits, there are also potential problems that can arise when implementing this approach in EFL writing classes. This article explores some of the common challenges and suggests strategies for educators to address these issues effectively.